Dietary phytochemical index associated with cardiovascular risk factor in patients with type 1 diabetes mellitus - Delshad Aghdam, Saeideh (BMC Cardiovasc Disord, 2021)
BACKGROUND: Dietary phytochemical index (DPI) is useful and inexpensive method to identify the role of phytochemicals on cardiovascular disease (CVD) risk factors. This study aimed to assess the relationship between DPI and CVD risk factors in patients with type1 diabetes mellitus. METHODS: A total of 261 participants aged 18–35 years with T1DM were enrolled in this cross-sectional study to assess the relationship between DPI and CVD risk factors. Anthropometric measurements, blood lipids, glucose, and antioxidant level were measured. Food intakes were determined using a food frequency questionnaire to calculate DPI. Logistic regression was used. RESULTS: The mean age of participants was 25 years. After adjustment for potential confounders, participants in the highest tertile of DPI had 88 % lower chance of hyperglycemia (P for trend = 0.020), 81 % lower chance of low high-density lipoprotein cholesterol (HDL-C) (P for trend = 0.030) and 98 % lower chance of high low-density lipoprotein cholesterol to HDL-C ratio (P for tend = 0.040). There were no relationships between DPI and other CVD risk factors. CONCLUSIONS: Although higher intake of phytochemical-rich foods had a beneficial effect on some risk factors of CVD, more studies more studies are warranted to corroborate the present findings.